Teacher Behavior With Upper Elementary School Students in the Social Margins of Their Classroom Peer Group - Hendrickx, Marloes M. H. G.; Mainhard, Tim; Cillessen, Antonius H. N.; Brekelmans, Mieke (Frontiers in Education, 2020)
Students in the social margins of their classroom peer group, in the current study operationalized as students who are often by themselves, do not belong to a group of friends, and are unpopular, are hampered in their social development. In line with social referencing, which states that teachers can affect peer perceptions through their interactions with students, we hypothesized that teachers may contribute to the social participation and integration of these students, by modeling frequent and positive interaction with them. We therefore explored teacher behavior with socially marginalized students, and how these interactions were related to changes in the severity of their social marginality over time. Multilevel analyses were performed with a sample of Dutch 824 fifth-grade students (Mage = 10.63) and their 32 teachers. Teachers had less frequent interactions with students in the social margins of the group, particularly when these students were unpopular. Nonetheless, we found some evidence for a social referencing mechanism: latent growth modeling showed that when teachers acted less negatively towards socially marginalized as well as rejected students, they became more socially integrated in their peer-group over time.